Adapting English Instruction Amidst the Endemic Transition of COVID-19: A Case Study at SMP Negeri 1 Motui - Tri Akbar Hasmun; Kamaluddin Kamaluddin; Muhammad Yazid Abd. Rahim Gege (Journal of Language Education and Educational Technology (JLEET), 2024)
This study investigates the dynamics of English learning activities at the junior high school level within SMP Negeri 1 Motui, situated in the Motui District, Konawe Utara Regency, during the transition period to the endemic phase of COVID-19. It aims to explore both the activities conducted by English teachers in the classroom and students' perceptions of teaching methodologies. The theoretical framework draws upon Richard and Rodgers' (2014) principles of English language teaching to analyze classroom practices. Employing a qualitative descriptive approach, the study involved 24 students and English teachers from SMPN 1 Motui. Data collection included observation sheets and interview transcripts. Findings reveal that the English learning process in the classroom aligns with 14 out of 15 criteria outlined by the theoretical framework, encompassing physical engagement, instructional coherence, task assignments, scaffolding techniques, thematic integration, and more.